2021
DOI: 10.2147/ccid.s318603
|View full text |Cite
|
Sign up to set email alerts
|

Illness Acceptance as the Measure of the Quality of Life in Moderate Psoriasis

Abstract: Introduction Psoriasis is a chronic disease with intermittent flares and remissions. Each individual perceives the disease, its somatic effects, resultant dysfunction and related problems differently. This attitude is primarily determined by one’s characterological traits and type of illness. A primary response to the diagnosis can be denial, underestimation, acceptance or overestimation of the disease. The aim of the study was to analyze the level of illness acceptance and its effect on the quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Similar findings were also observed in patients with melanoma, where correlation analyses revealed that illness denial was significantly associated to higher levels of psychological distress [74]. In patients with plaque psoriasis, Jankowiak et al [75] showed that denial, defined as a lower level of illness acceptance, was significantly associated with impaired quality of life.…”
Section: Clinical Outcomementioning
confidence: 56%
“…Similar findings were also observed in patients with melanoma, where correlation analyses revealed that illness denial was significantly associated to higher levels of psychological distress [74]. In patients with plaque psoriasis, Jankowiak et al [75] showed that denial, defined as a lower level of illness acceptance, was significantly associated with impaired quality of life.…”
Section: Clinical Outcomementioning
confidence: 56%
“…Each individual perceives the disease, its somatic effects, resultant dysfunction, and related problems differently. This attitude is primarily determined by one's character traits and type of illness [2].…”
Section: Introductionmentioning
confidence: 99%
“…Acceptance of illness was originally described as acceptance of the sense of loss [17]. It is a psychological state in which illness is perceived as part of the individual's perception of reality and no longer seen as a limiting factor for the individual.…”
Section: Introductionmentioning
confidence: 99%